Systematic Review of Virtual Reality Solutions Employing Artificial Intelligence Methods - Ribeiro de Oliveira, Taina; Moura da Silva, Matheus; Nepomuceno Spinasse, Rafael Antonio; Ludke, Gabriel Giesen; Ruy Soares Gaudio, Mateus; Iglesias Rocha Gomes, Guilherme; Cotini, Luan Guio; Vargens, Daniel; Schimidt, Marcelo Queiroz; Varejao Andreao, Rodrigo; Mestria, Mario (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2021)
This paper first presents a systematic literature review of artificial intelligence (AI) methods used in virtual reality (VR) solutions. Based on the systematic literature review, a methodology for locating existing studies, selecting and evaluating contributions, performing analyses, and synthesizing data was proposed. We used search engines, such as Google Scholar and databases such as Elsevier's Scopus, ACM Digital Library, and IEEE Xplore Digital Library. A set of inclusion and exclusion criteria was used to select documents. The results showed that the AI scientific technique most applied in VR applications is machine learning. The findings revealed several fields adopting real-world applications that employ AI in VR: human–robot interaction, emotion interaction and behavior recognition, education, agriculture, transport, manufacturing, and health.